Martin Luther King - Bains, Rae.; Frenck, Hal (Mahwah, N.J. : Troll Associates, 1985)
A biography of a courageous leader in the civil rights movement who championed nonviolent protest and "had a dream" of equality for all.
4.1
3-6
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968.; King, Martin Luther, Jr., -- 1929-1968.; Afro-Americans -- Biography -- Juvenile literature; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; Afro-Americans -- Civil rights -- Juvenile literature; Civil rights workers; Afro-Americans -- Biography; Civil rights workers; Blacks -- Biography